Kepemimpinan Inovatif dan Pemahaman Guru terhadap Merdeka Belajar di Sekolah Dasar - Hijrah, Sesep Ferdiansyah Syaiful (Jurnal Didaktika Pendidikan Dasar, 2025)
The objective of this research is to provide a comprehensive overview and empirical evidence regarding the influence of school principals who are graduates of the Pendidikan Guru Penggerak Program on teachers’ understanding of the Merdeka Belajar concept in public elementary schools in the Sukagumiwang District, Indramayu Regency, West Java Province, using a sample of 30 teachers. The study employs a quantitative method with data collection techniques through questionnaires. The questionnaire utilized is a closed-ended questionnaire using a Likert scale. Data were analyzed using univariate analysis, linear regression analysis with t-tests and coefficient of determination (R²), as well as Pearson product-moment correlation tests, conducted using SPSS Version 29.0 for Mac. Based on the results and discussion, it is concluded that school principals’ leadership who are graduates of the Pendidikan Guru Penggerak program in four aspects (1) ability to focus on groups; (2) providing encouragement and motivation; (3) delegating authority; and (4) stimulating creativity; is consistent with teachers’ understanding of the Merdeka Belajar concept. This research concludes that the leadership of principals who graduated from the Pendidikan Guru Penggerak program significantly impacts teachers’ understanding of the Merdeka Belajar concept, with an influence of 90.40%, while the remaining 9.60% is influenced by other factors.